Behaviour of eccentrically loaded circular recycled aggregate concrete-filled stainless steel tube stub columns - Zhong, Yukai (2023)
This paper presents an experimental and numerical study of eccentrically loaded circular recycled aggregate concrete-filled stainless steel tube (RACFSST) stub columns. The testing programme was conducted on twelve specimens designed with different stainless steel tube section sizes and recycled coarse aggregate replacement ratios, and included tensile coupon tests, concrete cylinder tests and eccentric compression tests. The test results, including the failure loads and modes, load–mid-height lateral deflection curves and evolution of neutral axis, were reported and discussed. Following the testing programme, a numerical modelling programme was conducted, with finite element models developed and validated against the test results and then employed to perform parametric studies to generate further numerical data. The confinement effects were analysed based on the numerical data. The relevant design interaction curves, as set out in the European code, American specification and Australian/New Zealand standard, were assessed for their applicability to circular RACFSST stub columns under combined compression and bending. On the basis of the quantitative and graphical assessments, it has been found that (i) each set of codified design interaction curve leads to similar assessment results for eccentrically loaded circular RACFSST stub columns with different recycled coarse aggregate replacement ratios and (ii) the failure load predictions from the codified design interaction curves are conservative.